2018
DOI: 10.1002/hed.25565
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of C‐reactive protein/albumin ratio for patients with hypopharyngeal and laryngeal cancer undergoing invasive surgery involving laryngectomy

Abstract: Background The C‐reactive protein/albumin (CRP/Alb) ratio has been recently established as a prognostic indicator in various cancer types. However, few reports regarding the prognostic value of the CRP/Alb ratio in head and neck cancer exist. This study aimed to investigate the significance of the CRP/Alb ratio in clinical outcomes after invasive surgery involving laryngectomy for hypopharyngeal and laryngeal cancer. Methods We evaluated 56 patients who underwent total laryngectomy or total pharyngolaryngectom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 40 publications
1
17
1
Order By: Relevance
“…The preoperative nomogram's primary advantage is that it can predict individualized 3-and 5-year survival, thereby helping surgeons to identify patients who are likely to benefit from extensive surgery and multidisciplinary management. Nomograms have been used as prognostic adjuncts for several types of cancer; thus, they play a major role in personalized oncology medicine (Kao et al, 2018;Kattan et al, 1998;Li et al, 2016). In the present study, a high CAR was strongly associated with a more advanced disease stage, lymph node metastasis with ENE, DOI >10 mm, need for adjuvant therapy, and shorter survival.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…The preoperative nomogram's primary advantage is that it can predict individualized 3-and 5-year survival, thereby helping surgeons to identify patients who are likely to benefit from extensive surgery and multidisciplinary management. Nomograms have been used as prognostic adjuncts for several types of cancer; thus, they play a major role in personalized oncology medicine (Kao et al, 2018;Kattan et al, 1998;Li et al, 2016). In the present study, a high CAR was strongly associated with a more advanced disease stage, lymph node metastasis with ENE, DOI >10 mm, need for adjuvant therapy, and shorter survival.…”
Section: Discussionsupporting
confidence: 52%
“…In the present study, we assumed the CAR cutoff of 0.195 may be useful for predicting OS and DFS in patients with OSCC, and this index may have a cutoff specific for primary tumors at different sites (He et al, 2016;Kuboki et al, 2019;Park, Kim & Kim, 2016;Yu et al, 2017). Among all studies on head neck cancers, Wang et al (2019) reported the highest cutoff CAR value of 0.525 as a prognostic indicator in patients with OSCC; their study, however, included high proportions of patients aged >60 years and with advanced disease stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a Taiwanese group published various studies on the prognostic role of CRP in oral cancer and could consistently demonstrate an association between elevated CRP levels and survival [34][35][36]. More recently, pre-therapeutic indices of systemic inflammation based on CRP and albumin have been found to provide prognostic information in nasopharyngeal and laryngeal cancer patients [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The CAR was found to be a more accurate independent prognostic indicator than other indicators such as GPS, NLR, and PLR in predicting prognosis of various types of cancer. [21][22][23] However, to the best of our knowledge, the prognostic value of CAR in ENKTL has never been investigated. Therefore, we performed the retrospective analysis with a comparatively large sample size to evaluate the prognostic significance of CAR in patients with ENKTL, and we also developed an easily applicable prognostic nomogram based on NKPI with readily accessible parameters for the estimation of clinical outcome in ENKTL.…”
Section: Introductionmentioning
confidence: 99%